Synthesis and Structure Elucidation of 1,3 bis(p-Hydroxyphenyl)urea - HARI PURNOMO; UMAR ANGGARA JENIE; AGUNG ENDRO NUGROHO; HARNO DWI PRANOWO (JURNAL ILMU KEFARMASIAN INDONESIA, 2016)
Paracetamol is a well known and commonly used analgesic-antipyretical agent. However, it exhibits hepatotoxic side effect if used for the long term or using exessive dose (10-15 g for single dose). A new compound of 1.3 bis (p-hydroxyphenyl)urea (code-name as HP2009) is an analgesic agent, and it is predicted that its hepatotoxic side effect is lower than that of paracetamol. The compound HP2009 was succesfully synthesized. The result showed that by using molar ratios of p-aminophenol and urea 2:9.5, pH 1 for reaction condition, refluxing for about 1 hr and evaporating time was set up for 30 minutes, the yield of HP 2009 will be 99.49%. The crystals obtained was characterized using spectroscopic methods, and showed undoubtedly that the product was 1.3 bis(p-hydroxyphenyl)urea.